Design of an adaptive controller in constant pressure grinding of natural diamond cutters. (1st January 2011) - Du, Wenhao; Liu, Xingbao; Sun, Tao; Wang, Baorui
Natural diamond cutters are critical cutting tools applied in nano science and technology fields. The properties of diamond crystal, which are advantages for making high precision cutters, also bring difficulties to the cutter grinding process. In this paper, an adaptive control method is described based on principles of predictive functional control (PFC) method. With this method, an adaptive controller was designed in order to implement constant pressure grinding of natural diamond cutters. Firstly, a real-time grinding process model was constructed, taking account of time-variant characteristic of the wheel-cutter contact and the low stiffness of flexible stage in the practical grinding system. Then, parameters of PFC controller was calculated according to this model. Controller performances were simulated under three conditions of non-disturbance, model parameter mismatch, and time-variant disturbance. Simulation results show that performance of the designed controller is as good as desired, and the controller has enough capability to fit practical diamond cutter grinding process which has characteristics of non-linear and time variance.